2007
DOI: 10.1515/cam.2007.005
|View full text |Cite
|
Sign up to set email alerts
|

Who gets to talk? An alternative framework evaluating companion effects in geriatric triads

Abstract: Most studies evaluating companion effects on medical triadic interaction focus on the doctors' part, e.g., how the companion's presence diverts doctors' attention away from the patient. In contrast to this mainstream approach, the current research proposes an alternative framework by focusing on the patient parties—especially on how companion participation reshapes the discourse sequences where patient parties provide information, and how it affects patient full turns and priority in providing complete first-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…While the role of third parties in medical communication has been explored in several studies of actual patient provider communication [2123], the impact of the presence of a standardized spouse on the performance of SPs has not been previously reported. The degree of tailoring within genetic counseling communication must also be considered when interpreting these observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of third parties in medical communication has been explored in several studies of actual patient provider communication [2123], the impact of the presence of a standardized spouse on the performance of SPs has not been previously reported. The degree of tailoring within genetic counseling communication must also be considered when interpreting these observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…Green(14) found that patients who were accompanied raised fewer conversational topics and participated less often in decision-making. Tsai(15) found that when Taiwanese patients were accompanied, they volunteered less information to physicians. Wolff(2) concluded that multiple studies have indicated accompanied patients are less verbally active and discussion is shifted toward biomedical information-giving and away from psychosocial exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Taiwan's proportion of older people is expected to rise further in the coming years, given increases in its population's longevity and recent sharp decreases in its birthrate. Nevertheless, language and communication studies which focused on ageing, older age or older people are still relatively rare in Taiwan, with important exceptions related to health/medical communication (Tsai, 2003(Tsai, , 2005(Tsai, , 2007(Tsai, , 2010(Tsai, , 2017(Tsai, , 2018, teacher-older-student communication (Chen, 2015a;Chen, 2019), in media communication (Chen, 2015b;Chen, 2015c;Chen, 2016), intergenerational first-encounter talks (Chen, 2017) and the discourse features of senior Alzheimer's patients (Lai, 2014, Lai & Lin, 2012. Uniquely, the current study examines casual talks between younger and older adults at their first encounters, with an interest on the cultural conceptualisation of older age and the discursive management of age-telling by older people.…”
Section: Gerontological Sociolinguisticsmentioning
confidence: 99%